IMPLEMENTASI SISTEM INFORMASI MULTIMEDIA MENGGUNAKAN TEKNIK PANORAMA VIEW 360 Derajat - Zaliluddin, Dadan; Berliani, Mega (Jurnal Sistem Informasi, 2023)
Technology is essential in this day and age since it makes practically all jobs easier to do. Technologies that are constantly developing and changing swiftly can easily access practically all data worldwide. In addition to being written, information can also be preserved as pictures or images. Modern picture technology, such as the 3600 panorama view, was developed from digital photos that were then made into panoramic photos. This study intends to make it easier to get information regarding Majalengka University's campus infrastructures. For this study, the researchers employed the Multimedia Development Life Cycle (MDLC) method because it is appropriate for planning and creating media applications that incorporate audio, video, and image media. The six stages of the MDLC process include idea, design, material gathering, assembly, testing, and distribution. According to the study, the University of Majalengka's facility information system, which employs the web-based Panorama View 3600 technique, is capable of providing accurate information about all the university's facilities and spaces. The study's finding is that each faculty's location, as well as any facilities or places that are available at the University of Majalengka, can be found on the website.